Analysis of Education Policy on the Implementation of Post-Covid-19 Distance Learning - Oktiarina, Vina; Syarifudin, Encep; Suherman, Suherman (research, training and philanthropy institution Natural Aceh, 2024)
Learning is a central aspect of the educational process essential in transferring knowledge and skills to individuals. However, when obstacles are caused by situations and conditions that do not allow direct/face-to-face learning in the classroom, then learning can be implemented online. Through the digital platform, teachers and students can connect virtually, cross the boundaries of distance and time, and utilize technology to learn. This research analyzes educational policies on implementing distance learning after Covid-19 to see the various problems faced. This research uses a qualitative method with a literature study approach. Data analysis will be carried out through selecting, comparing, combining, and sorting out various definitions, until relevant ones are found, and to overcome misinformation or avoid errors, inter-literature checking and re-reading of literature are carried out. The result of this research is that the implementation of distance learning is still faced with various obstacles. These constraints include limited social interaction between teachers and students, limited learning services that can be provided, the need for understanding the use of learning applications, internet-related constraints, and the economy. This research shows the need for efforts to overcome these obstacles so that distance learning can run more effectively and evenly.